A 1‐Million‐Year Record of Environmental Change in the Central Mediterranean Sea From Organic Molecular Proxies. Issue 10 (23rd October 2021) - Martínez‐Dios, Ariadna; Pelejero, Carles; Cobacho, Sara; Movilla, Juancho; Dinarès‐Turell, Jaume; Calvo, Eva
Abstract: The Mediterranean Sea is particularly sensitive to climate oscillations and represents a key location to study past climatic and oceanographic changes. One valuable source of paleoceanographic information is through molecular biomarkers in deep sea sediments. This approach has been applied in a number of studies in this basin, but only covering the most recent glacial/interglacial cycles. Here we present, for the first time in the Mediterranean Sea, a molecular biomarker record from the Strait of Sicily that covers the last million years until the present, almost continuously. We present data on alkenone derived U 37 K' index sea surface temperatures (SST) and provide insights on the evolution of the phytoplankton community composition and terrestrial inputs through the analysis of the concentrations of alkenones, brassicasterol and long‐chain alcohols. The U 37 K' ‐SST record followed a climatic evolution modulated by glacial/interglacial cycles with a marked increase in the 100 kyr‐amplitude of the glacial cycles at ∼430 ka, coincident with the Mid‐Brunhes transition. In addition, SSTs were consistently higher compared with other records in the western Mediterranean, indicative of the progressive warming that surface waters experience along their transit from the Strait of Gibraltar to the Central Mediterranean. Regarding the concentrations of alkenones and brassicasterol, they displayed distinct alternate peaks, some of them coeval with the deposition of sapropels. This suggests that different environmental and oceanographic conditions characterized each sapropel which, together with changes in terrestrial inputs and the degree of oligotrophy, induced the alternate proliferation of coccolithophores and diatoms. Plain Language Summary: The Mediterranean Sea, located between subtropical and temperate latitudes, is a very sensitive area to changes in climate, becoming an ideal location for studying past climate changes. One valuable source of information about past ocean conditions are fossil molecules—or biomarkers—produced by microalgae or terrestrial plants, that end up buried in deep sea sediments. This technique has been widely used in the Mediterranean Sea to infer sea surface temperatures (SST), but only covering the last ∼500, 000 years. In this work, we studied a deep sea sediment core from the Strait of Sicily (Central Mediterranean), that covers a much longer time scale, the last million years until the present, almost continuously. By analyzing fossil molecules in this core, we were able to reconstruct SST and infer changes in microalgae community and their relationship with terrestrial inputs to the ocean. Our data indicate that the SST evolution in the Central Mediterranean followed global trends but with slightly warmer temperatures compared to other records in the Western Mediterranean. Moreover, the studied biomarkers pointed towards alternate periods of proliferation of diatoms and coccolitophores. Some of these events matched the Mediterranean sapropels which, particularly in the eastern basin, were times of significantly enhanced primary productivity, surface stratification and deep‐water anoxia. We suggest that different environmental conditions during each sapropel, related to the nutrient supply and the degree of oligotrophy, may explain the alternate development of these algal groups. Key Points: A molecular biomarker record covering the last 1 million years is presented, for the first time, in the Mediterranean Sea Sea surface temperatures in this new record from the Sicily Strait were consistently warmer than other records located further to the west Alternate peaks of alkenones and brassicasterol coeval to several sapropels suggest distinct proliferation of coccolitophores and diatoms